Analysis of 5G NR coverage capability at 2.6 GHz - Xinkai CUI; Hao LI; Xiangchuan GAO; Huan YANG (Dianxin kexue)
The current research on 5G new air interface is mainly concentrated in the middle and high frequency bands.The low frequency band re-cultivation used by 4G is of great significance for 5G-scale contiguous networking,but there are few studies.On the basis of discussing the factors affecting the radio transmission capability,the urban outdoor non-line-of-sight propagation model of 3GPP TR38.901 was selected,and the current mainstream air interface parameters were used to simulate the multi-system main physical channel propagation capability.By comparing the coverage capabilities of the same physical channels in the 4G and 5G NR bands,the 5G NR primary channel coverage capability in the 2.6 GHz band can achieve contiguous coverage on the existing 4G basis.